'CHOKUBAISHO' AS A WAKAYAMA FRUIT FARMER DIRECT SALES SYSTEM IN JAPANESE AGRI-FOOD NETWORK GOVERNANCE - Dwi Sumara Hati; Kurniawaty Iskandar; Kosuke Mizuno (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2021)
The global food system always faces threats and challenges. However, on the other hand, it is an opportunity for the Japanese civil society social movement to play an active role in building a just and sustainable food system. Chisan Chishou movement (local product, local consumption campaign) provides excellent opportunities for farmers in Prefecture Wakayama Japan to target local potential, with transparent price and added value through the Sanchoku （産直）or direct sales system. The Japanese food distribution chain is systemically coordinated below shade Kyoudou kumiai (協同組合) or JA (Japan Agricultural Cooperative), as a prominent entity in Japanese agri-food network governance. Qualitative method selected in explaining paradigm social capital and network in its role to achieve prosperity and regional economic development, by considering indicator non-physical such as the value of 'trust' and reciprocity in 'network' as the essential attributes of the social capital. The study case of farmer as a member of Japan Agricultural Cooperative (JA) Wakayama Prefecture describes how the Chokubaishou system is a strategy for the farmer to resolve problem profitability on the Chokubaishou JA system with the character of quality products at low prices. The non-binding JA membership system is a benefit for farmers in obtaining agricultural facilities and securing sales channels with a more stable market and low risk of operating costs. The mutual dependence on relational cooperation and 'trust' on this agri-food network mechanism has become a 'safety guard' for farmers, and JA perpetuates the sales business that profitable and sustainable.Keywords; Social Capital; Direct Sales System, Chokubaishou; Agri-Food Network